2018
DOI: 10.1080/21663831.2018.1477846
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric performance of silicon with oxide nanoinclusions

Abstract: Silicon nanoparticles produced via a plasma-based technique have been sintered into bulk nanostructured samples. These samples have micron-sized crystalline domains and contain well-dispersed oxide nanoinclusions. We have compared the thermoelectric performance of such structure to that of a control sample produced by sintering ball-milled silicon powders. The control sample has lower precipitate density and is composed of nanograins. Despite the stark difference in nanostructure, both samples have comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…These variations became smaller with increasing amounts of added SrTiO 3 , resulting in a larger μ value in the composite sample at high temperature than that for the single-phase SiGe. Although the oxide nanoinclusions in SiGe have been reported to act as a phosphorus reservoir, no such behavior was observed in our data. In contrast, the addition of SrTiO 3 suppresses the rise of n at high temperatures, indicating that the oxide phase traps the precipitated phosphorus (as observed in Figure ) and prevents the formation of a solid solution of phosphorus in Si at high temperature.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…These variations became smaller with increasing amounts of added SrTiO 3 , resulting in a larger μ value in the composite sample at high temperature than that for the single-phase SiGe. Although the oxide nanoinclusions in SiGe have been reported to act as a phosphorus reservoir, no such behavior was observed in our data. In contrast, the addition of SrTiO 3 suppresses the rise of n at high temperatures, indicating that the oxide phase traps the precipitated phosphorus (as observed in Figure ) and prevents the formation of a solid solution of phosphorus in Si at high temperature.…”
Section: Resultscontrasting
confidence: 94%
“…36,37 Because the carrier concentration decreased with increasing SrTiO 3 content (Figure 5c), when the SrTiO 3 content increased to ≥5 wt %, σ significantly decreased, indicating that the contribution of n to σ becomes more significant than that of the mobility. The rise in n at high temperature can be attributed to the increased solubility of phosphorus in silicon, 33,38 which induced an additional reduction of μ (as discussed above) coming from ionized impurity scattering. These variations became smaller with increasing amounts of added SrTiO 3 , resulting in a larger μ value in the composite sample at high temperature than that for the single-phase SiGe.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Favier et al demonstrated that nanocompositing-associated lattice interfaces scatter thermal carriers more effectively than do grain boundaries. Therefore, adding nanoinclusions is better than producing nanograin structures to improve ZT . Thus, nanocompositing is one of the best strategies for modifying the interconnected σ, α, and κ .…”
Section: Introductionmentioning
confidence: 99%
“…Bulk silicon is not an efficient thermoelectric material due to its high thermal conductivity [10,11]; however, it provides an excellent platform for studying the role of design parameters on transport properties, since its bulk properties are extremely well characterized. This study is partially motivated by our recent findings suggesting that oxide inclusion, spontaneously nucleated during the sintering of silicon nanoparticles, can be effective at improving thermoelectric power conversion [12]. While the mechanism is attractive, this synthesis route is problematic since the thermodynamically driven nucleation of oxide inclusions is difficult to control, meaning that inclusions' size and density are not easily and independently tunable.…”
Section: Introductionmentioning
confidence: 99%